Analysis of outcome in dogs that undergo secondary amputation as an end‐point for managing complications related to limb salvage surgery for treatment of appendicular osteosarcoma. (24th June 2019) - Wustefeld‐Janssens, Brandan G.; Séguin, Bernard; Ehrhart, Nicole P.; Worley, Deanna R.
Abstract: Appendicular osteosarcoma (OSA) remains a prevalent musculoskeletal cancer in dogs and definitive local control followed by adjuvant cytotoxic chemotherapy is considered the gold standard approach. Several studies support surgical limb salvage as a means of local control with similar outcomes compared with limb amputation. Complications are well described for limb salvage but little is known of dogs that undergo secondary amputation as a result of complications and outcomes specific to this group. A retrospective analysis of dogs in an institutional primary bone tumour registry was performed to identify dogs diagnosed with histologically confirmed OSA treated with surgical limb salvage with a technique that required an implant to reconstruct the osseous defect. A total of 192 dogs were identified with 31 dogs undergoing secondary amputation representing a limb preservation rate of 84%. A total of 111 dogs were analysed: 31 secondary amputation cases and 80 controls were selected for comparison. The most common reasons for secondary amputation were local recurrence (LR) and surgical site infection (SSI), with odds ratios of 3.6 and 1.7, respectively. Dogs that underwent secondary amputation had a significantly ( P = .05) longer median disease specific survival time (ST) (604 days) compared with the control group (385 days). Dogs lived for a median of 205 days beyond secondary amputation and 97% had good functional outcome. Significant independent factors that positively influenced ST were secondary amputation, moderate SSI, severe SSI and age.